Ambulatório de avaliação pré-anestésica: nível de satisfação de pacientes e cirurgiões de um hospital público da região Centro-Oeste do Brasil - Jacintho, Luivya Cristina (2022)
This research aimed to evaluate the level of satisfaction in patients and surgeons of a reference hospital on the pre-anesthetic evaluation outpatient clinic. This is a descriptive, cross-sectional study based on primary data in which a questionnaire was used for each of the two groups, with questions related to knowledge, use and satisfaction about the pre-anesthetic evaluation outpatient clinic. Five patients and 55 surgeons from various specialties participated in the research. The research was approved by the Ethics Committee of the Federal University of Mato Grosso do Sul, under opinion No 3.950.987. The results show that all patients considered the pre- anesthetic consultation as convenient, had satisfactory answers to their questions and doubts, would perform the evaluation in future surgeries and as to the degree of satisfaction classified as very satisfied. Of the surgeons, 35% were unaware of the work of the outpatient clinic, but 87% expressed satisfaction with it, evidencing the benefits of pre-anesthetic consultation for surgical procedures. It is concluded that it is necessary to disseminate the activities of the outpatient clinic and the implementation of a referral flowchart, with a view to complying with the recommendation of the Federal Council of Medicine on the pre-anesthetic evaluation, either for elective and urgent procedures.